Homeostasis-Stimulated Proliferation Drives Naive T Cells to Differentiate Directly into Memory T Cells - Cho, Bryan K. (The Rockefeller University Press, 2000)
The developmental requirements for immunological memory, a central feature of adaptive immune responses, is largely obscure. We show that as naive CD8 T cells undergo homeostasis-driven proliferation in lymphopenic mice in the absence of overt antigenic stimulation, they progressively acquire phenotypic and functional characteristics of antigen-induced memory CD8 T cells. Thus, the homeostasis-induced memory CD8 T cells express typical memory cell markers, lyse target cells directly in vitro and in vivo, respond to lower doses of antigen than naive cells, and secrete interferon γ faster upon restimulation. Like antigen-induced memory T cell differentiation, the homeostasis-driven process requires T cell proliferation and, initially, the presence of appropriate restricting major histocompatibility complexes, but it differs by occurring without effector cell formation and without requiring interleukin 2 or costimulation via CD28. These findings define repetitive cell division plus T cell receptor ligation as the basic requirements for naive to memory T cell differentiation.